The Eastern Partnership of the EU – the Challenges and the Opportunities in the Context of the Ukraine's Crisis - Gheorghe Ciascai (CES Working Papers, 2014)
The aim of this paper is to highlight the political limits and the strategic and geopolitica ldilemmas of the European Union's approach concerning the Eastern Neighbourhood. For this reason, the research will examine the main steps of the implementation of the Eastern Partnership and the main consequences and dilemmas of this implementation for the Eastern European Partners, especially for Ukraine. Also, the paper will investigate the impact of the Eastern Partnership for the Russian approach concerning the near western abroad and the European Union.
Keywords: F51; F53; F59; 330; European Union; Eastern Neighbourhood; Eastern Partnership; security; geopolitics; crisis Romania